2022
DOI: 10.22219/fths.v5i1.18979
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Fisikokimia dan Organoleptik Stik dengan Formulasi Tepung Lemon (Citrus limon L) dan Pati Jahe Merah (Zingiber officinale var Rubrum)

Abstract: Abstract. Sticks are a type of long, flat-shaped pastry. The development of sticks products with other ingredients such as lemon and red ginger is expected to increase the level of antioxidant activity. Lemon contains citric acid, vitamin C and flavonoids, asa natural antioxidant. The rhizome of red ginger contains gingerol, which also has antioxidant properties. The purpose of this study is to make healthy snacks with antioxidant properties. The first step in this study is the production of lemon powder and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
2
2
3
Order By: Relevance
“…Secang wood extract has a total flavonoid content of around 0.0667 mg/g (Neswati & Ismanto, 2018). Apart from that, red ginger also contains gingerol and shogaol which are also flavonoids (Verenzia et al, 2022). Red ginger extract has a total flavonoid content of around 46.56 g/g (Pratoko et al, 2018).…”
Section: Supporting Qualitymentioning
confidence: 99%
“…Secang wood extract has a total flavonoid content of around 0.0667 mg/g (Neswati & Ismanto, 2018). Apart from that, red ginger also contains gingerol and shogaol which are also flavonoids (Verenzia et al, 2022). Red ginger extract has a total flavonoid content of around 46.56 g/g (Pratoko et al, 2018).…”
Section: Supporting Qualitymentioning
confidence: 99%
“…Padahal limbah pati jahe tersebut dapat dimanfaatkan untuk pembuatan olahan jahe yang lain, misalnya sebagai filler pada pembuatan permen jahe. Selain itu, pati jahe juga dapat dimanfaatkan sebagai bahan baku sirup glukosa (Andriani & Yunianta, 2014) maupun kerupuk stik (Verenzia et al, 2022). Oleh karena itu perlu dilakukan pelatihan mengenai pemanfaatan limbah pati jahe dan pembuatan permen jahe sebagai upaya untuk diversifikasi produk sekaligus untuk memanfaatkan limbah.…”
Section: Pendahuluanunclassified
“…Pati jahe merah adalah pati yang terbuat dari jahe merah yang telah diendapkan kemudian dikeringkan dan dijadikan bahan baku pada produk pangan (Verenzia et al, 2022). Pengolahan jahe merah instan di KWT Srikandi akan menghasilkan limbah berupa pati jahe merah, seperti terlihat pada Gambar 3.…”
Section: Kegiatan Pelatihan Pengolahan Limbah Pati Jaheunclassified
See 1 more Smart Citation
“…That was believed that consuming red ginger can add energy to the body. Verenzia et al (2022) reported that the higher carbohydrate content in powdered red ginger would produce a greater energy level. That explained the consumption of red ginger can increase energy for the body (Verenzia et al, 2022).…”
Section: Carbohydrate Levelsmentioning
confidence: 99%